Increasing sheep production through litter size in a Moroccan harsh environment - Bourfia M.; Benlekhal A.; Essaadi A. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
In Morocco, there is a need for a high reproductive rate to cope with the growing national demand for meat sheep. Besides the adaptation to the harsh environment of its large breeding area, the Beni Guil showed a potential for twinning in pastoral systems. As an alternative, a synthetic breed with equal contributions of the Beni Guil and the D'man had high reproductive rates in station that need checking by field tests. The experiment should continue to figure out the suitability of these two alternatives to the local environmental conditions of eastern Morocco that is mainly devoted to sheep production.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)